Scientific rationale for changing lower water temperature limits for triathlon racing to 12°C with wetsuits and 16°C without wetsuits - Saycell, J.; Lomax, M.; Massey, H.; Tipton, M. (British Journal of Sports Medicine, 2018)
Objectives To provide a scientific rationale for lower water temperature and wetsuit rules for elite and subelite triathletes.